1975
DOI: 10.1177/0310057x7500300303
|View full text |Cite
|
Sign up to set email alerts
|

Severe Histamine Mediated Reactions to Intravenous Drugs Used in Anaesthesia

Abstract: SI',Jere histamine mediated reactions to intrw(}clloltS drltgs ltsed ill anaesthesia may occur as a result of anaphylactic and anaphylactoid reactions. The incidence is rare, but appears to be increasing, The difficulties in diagnosing sltch reactions and in determining the dm{!. responsible and ho1.£' these difficulties hm.'c led to confllsionin the literatllre are discussed. Six cases of SC1 ' cre histamine mediated reactions are presented and detailed analyses of the drugs in these and other reported reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(18 citation statements)
references
References 88 publications
(36 reference statements)
1
17
0
Order By: Relevance
“…In France (11)(12)(13)(14), Australia (15)(16)(17)(18) and Great Britain (19)(20)(21)(22), follow-up investigations have been carried out after anaphylactic reactions in anaesthesia for the past 20-30 years. In France, surveys with results of follow-up have been published (13,23,24) for large numbers of patients, and these have repeatedly shown that neuromuscular blocking agents (NMBAs) are the most common causative agent, followed by latex and antibiotics.…”
Section: Causesmentioning
confidence: 99%
“…In France (11)(12)(13)(14), Australia (15)(16)(17)(18) and Great Britain (19)(20)(21)(22), follow-up investigations have been carried out after anaphylactic reactions in anaesthesia for the past 20-30 years. In France, surveys with results of follow-up have been published (13,23,24) for large numbers of patients, and these have repeatedly shown that neuromuscular blocking agents (NMBAs) are the most common causative agent, followed by latex and antibiotics.…”
Section: Causesmentioning
confidence: 99%
“…The anaphylactic reactions to dextran administered intravenously are well documented (5). During the last few years anaphylactic reactions even after intraperitoneal administration have been reported (1).…”
Section: 23 24 28)mentioning
confidence: 99%
“…The solubilizing agent for Saffan Ò was a polyethoxylated castor oil, Cremophor Ò -EL, which caused histamine release in animals by stimulating mast cell degranulation. This histamine released caused unacceptable adverse events (Clarke et al, 1975;Fisher, 1975;Dodman, 1980;Ennis & Lorenz, 1985). Because alfaxalone has a wide margin of safety, a formulation containing no Cremophor Ò -EL has been a target of research for some years (Brewster et al, 1989).…”
Section: Introductionmentioning
confidence: 99%